MINIMASI PRODUK CACAT DENGAN METODE DMAIC SIX SIGMA DI LANTAI PRODUKSI STAMPING PT XYZ - Ayu Putri Wardini (2021)
PT XYZ is a company that engaged in the manufacture of two-wheeled components. PT XYZ consists of a stamping and rod brake production floor. The processes on the stamping production floor are shearing, blanking, bending, and final inspection and packaging. From the data obtained in June - December 2020, it is known that 4 months have passed the company's defect tolerance limit, which is more than 3%. The types of defects found in this company are visual defects, blanking defects, bending defects, and bending remake defects. Therefore, process quality improvement is needed that aims to reduce the number of defective products. The Six Sigma method is also included in one of the quality control. The Six Sigma method used in this research is the DMAIC (Define. Measure. Analyze, Improve and Control) cycle. Based on the calculation, knowing that the average sigma value obtained 4.0218 with 6113.4350 Defects per million opportunities (DPMO). By applying improvements to the company, the sigma value increased by 0.3967 and the DPMO value decreased by 4247.